非小细胞肺癌患者肿瘤组织与外周血中EGFR表达相关性研究 (Zhongguo Fei Ai Za Zhi, 2010)
BACKGROUND AND OBJECTIVE: It has been proven that EGFR plays an important role in cell proliferation, and has predictive values for diagnosis and prognosis. The aim of this study is to investigate the correlation between the expression of EGFR in tumor tissue and peripheral blood in non-small cell lung cancer (NSCLC) patients. METHODS: The expression of EGFR was analyzed by real-time RT-PCR in 46 NSCLC tumor tissues and by ELISA in peripheral blood, compared with 10 patients with benign pulmonary diseases as control. RESULTS: Linear correlation analysis revealed there was a correlation of the expression of EGFR protein between peripheral blood and tumor tissue (P=0.016, R(2)=0.83). CONCLUSION: The expression of EGFR mRNA in tumor tissue was positively correlated with EGFR protein in plasma. Detection of protein in plasma may replace that in tumor tissue, providing a quicker and easier examination method for the patients lacking biopsy tissue.